DEFINITION OF THE FIELDS OF THE BEST PRACTICES OF EPC (M)-PROJECT MANAGEMENT ON THE BASIS OF THE ANALYSIS OF THE WORLD MARKET - A. Laznik (Вестник университета)
This article presents the results obtained within the framework of the dissertation research, after the analysis of the materials of the leading foreign institutes regarding the best application/implementation of the EPC (M)-projects. Based on the results, 15 most significant areas of EPC-projects management in the world market were identified, the strengthening of which leads to significant improvement of indicators in a certain direction and implementation of the project as a whole.